The Effect of Abutment Surface Roughness on the Retention of Implant-Supported Crowns Cemented with Provisional Luting Cement - Jalil Ganbarzadeh; Mohammad Reza Nakhaei; Farid Shiezadeh; Seyyed Mohammad Abrisham (Mashhad University of Medical Sciences, 2013)
Introduction: Surface roughness can increase the retention of castings by ridges and grooves that are microretentive. This study compared the retention of implant-supported crowns when used with 3 different surface roughness abutments and one temporary cement. Methods: Thirty solid abutments (ITI), 4 mm high, were divided into three groups randomly. In the first group, 10 abutments were roughened with sandblast (50-µm aluminum oxide) and in the second group, 10 abutments were roughened with diamond bur. The third group had no surface treatment. Then, thirty implant fixture analogs (ITI) were placed in the center of acrylic cylinders. After that a solid abutment was tightened on the each fixture analog with 35 N/cm force. Thirty base metal crowns were made on the 4 mm ITI abutment analogs using plastic coping. The prepared copings were cemented on the abutments by TempBond temporary cement and finally, crowns were pulled from the abutment in a universal test machine at a cross speed of 0.5cm/min. Results: The mean tensile strength in sandblasted, bur treated, and control group were 64.38±8, 91.37±7.19, and 58.61±1.93, respectively. Bur treated group showed higher tensile strength in comparison with two other groups. Conclusion: Surface modification of implant abutment by diamond bur may be an effective method to increase retention of crown when TempBond is used.